Biomechanical analysis of accuracy penalties-kicking performance for Turkish Soccer players: Group-based analysis without goalkeeper - Abdullah Arguz; Guebli Abdelkader; Nurtekin Erkmen; Samet Aktaş; Madani Reguieg; Yusuf Er (Physical Education of Students)
Background and Study Aim. It is stated that kinetic performance factors are important in the successful execution of accurate kick-penalties, thus, its offer excellent performance despite a substantial kinetic method change in their implementation. The aim of the study is to biomechanical analysis of accuracy penalties-kicking performance for Turkish soccer players.